Wages, Demographics, and Gender: Register Analysis among Doctorate Holders in Iceland - Staub, Maya; Hjálmsdóttir, Andrea; Rafnsdóttir, Guðbjörg Linda (Nordic Journal of Working Life Studies, 2024)
The percentage of female doctorate holders has steadily increased in the Western world. Despite this trend, there is a scarcity of studies addressing gender disparities among doctorate holders, within and outside academia. We analyze the earnings of Icelandic doctorate holders either in the fields of science, technology, engineering, and mathematics (STEM) or social sciences and humanities (SSH) and are employed within and outside academia. We contend that achieving gender-wage equality is crucial for doctorate holders, given that education worldwide is considered a means to empower women and a significant factor in reducing gender inequality and narrowing the pay gap. Our findings reveal a continuous gender gap in total earnings between the fifth and tenth career years regardless of the field of study or the employment being within or outside academia. Thus, our findings suggest that a Ph.D. does not improve women’s earning power enough to close the gender pay gap.